MANAJEMEN KAMPANYE PUBLIC RELATIONS DALAM SOSIALISASI PROGRAM TANGGAP COVID-19 - Muhammad Saifulloh; Muhammad Fikri Lazuardi (Universitas Prof. Dr. Moestopo (Beragama), 2021)
This research focuses on the activities of the PT Pelabuhan Tanjung Priok Public Relations Campaign on Covid-19 Response in the Tanjung Priok Port Area. The purpose of this study was to determine the planning of the Covid-19 Response Campaign carried out by the Public Relations of PT Pelabuhan Tanjung Priok and what media were used in the campaign process. The theory used in this research is the 4 Steps Of Public Relations from Cutlip and also the concept of 10 Stages Of Campaign Planning. The research approach uses descriptive qualitative with a constructivist paradigm. Data collection in this study was carried out by means of observation and in-depth interviews with informants who were involved in the process of implementing the Covid-19 Response Campaign with the object of PT Pelabuhan Tanjung Priok. The results of research from the Covid-19 Response Campaign carried out several stages in a comprehensive manner by forming a Covid Management Team together with the K3L and HR divisions. Considering the situation during the pandemic which limited activities outside the home, the Covid-19 Response Campaign was carried out by utilizing digital media such as Websites, Social Media, and the company's main internal channel, namely E-Office.